The Effects of the Talking Stick Learning Method with Talking Chips on Learning Outcomes - Sriutami, Heni; Lestari, Neta Dian; Januardi, Januardi (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this study was to find differences of learning outcomes using the Talking Stick Learning Method with Talking Chips. The information selection procedure uses documentation, perceptions, and questions, while the information testing strategy uses the F-test (One Way Anova). The perception result states that the normal value of the Talking Stick class students' learning exercise is 71.05% with the high size, while the average value of the Talking Chips class students' practice is 79.49% with the high model. Thus the Talking Stick class has a high active value compared to the Talking Chips class. Based on the results of observations of 89.47% with a good predicate, while the value of student learning outcomes after applying the Talking Chips learning technique was 69.2% with a good predicate. Based on the F (One Way Anova) test, Fount = 6.255 > F-table = 3.968, so it was found that there were differences in learning outcomes using the Talking Stick Learning Method with Talking Chips at SMA Negeri 7 Palembang.